Infeksi dalam Bidang Periodonsia - Dewi Nurul (Faculty of Dentistry, Universitas Indonesia, 2015)
Periodontal diseases are frequently suffered in patient of all ages. This condition consist of several signs and symptoms, etiology, pathogenesis, and response to treatment which seems almost similar. The classification of those diseases have been adjusted, lately in 1999. The major cause of these diseases is bacterial. Microorganisms acts to result in infection due to the influence of host response, genetic, local and systemic factors. Gingivitis condition has an irreversible status and periodontitis has to be overcome immediately to prevent from further destruction. Some steps of initial treatment and supporting treatment should be given to the patient, which is able to be done by all dentists.